PENGARUH PENERAPAN GOOD GOVERNANCE DALAM E-PURCASHING TERHADAP PENCEGAHAN KORUPSI - Lati Praja Delmana (Jurnal Ilmu Pemerintahan Widya Praja, 2019)
Cases of corruption in Indonesia, especially in the sector of government procurement of goods and services, continue to increase every year. The government has reduce the rate of corruption in the procurement through electronic procurement. But the reality of corruption is still increasing. The authors are interested in building a conceptual framework for good governance and incorporating elements of local culture in electronic procurement to reduce corruption. The principle of good governance in electronic procurement can prevent corruption by applying the principles of participation, transparency, responsiveness, effectiveness, efficiency, equity, strategic objectives, accountability and local cultural values. The purpose of this research is to get a clear and measurable conceptual framework in reducing corruption in government procurement of goods and services. This research method is to use literature review with content analysis. The results of this study are that corruption can be reduced by using electronic procurement if it uses the principles of good governance and there are controlling variables, namely internal supervision, law enforcement and improvement of facilities, infrastructure, leadership commitment and improvement of human resources to carry out electronic procurement according to the rules.